Epileptic pathology and mental handicap - Mazza, Salvatore; Azzoni, Antonella; Laudisio, Alfredo (Medicina e Morale, 1988)
The not uncommon association, in the same individual, of phenomena of an epileptic nature with a certain degree of mental handicap means that this pathology must be given special interest on both a scientific and a human and social level.